Age-related changes of ocular parameters in Korean subjects - Dae Woong Lee (Dove Medical Press, 2010)
Dae Woong Lee1, Joon Mo Kim1, Chul Young Choi1, Donghun Shin2, Ki Ho Park3, Jung Gon Cho41Department of Ophthalmology, Sungkyunkwan University School of Medicine, Kangbuk Samsung Hospital, Seoul, Korea; 2School of Medicine, University of Queensland, Brisbane, Queensland, Australia; 3Department of Ophthalmology, Seoul National University College of Medicine, Seoul, Korea; 4Yebon Eye Clinic, Seoul, KoreaAims: To evaluate the age-related variations of ocular parameters in Korean subjects.Methods: We recruited 314 normal subjects who visited the department of Ophthalmology between January 2007 and October 2007. Refraction, axial length, corneal curvature, white-to-white distance, anterior chamber depth, corneal endothelial cell density, and retinal nerve fiber layer (RNFL) thickness were measured using auto-refractive keratometer, intraocular lens master, noncontact specular microscope, and optical coherence tomography.Result: In correlation analysis, from 19 to 82 years, hyperopic shift showed a strong positive statistical correlation with age (r = 0.553, P < 0.001). Corneal curvatures increased (r = 0.221, P < 0.001), while axial length (r = -0.506, P < 0.001), anterior chamber depth (r = -0.491, P < 0.001) and white-to-white distance (r = -0.205, P < 0.001) decreased with age. Also, corneal endothelial cell density was lower in older patients than in younger patients (r = -0.409, P < 0.001). Compared to younger patients, RNFL thickness was lower in the older patients as well, in all quadrants (superior, r = -0.283, P < 0.001; inferior, r = -0.230, P < 0.001; nasal, r = 0.025, P = 0.676; and temporal, r = -0.393, P < 0.001). According to multiple regression analysis, out of the six parameters measured, only hyperopic shift, anterior chamber depth and corneal endothelial cell density (P < 0.05) had statistically significant correlation with age.Conclusion: Some of the ocular parameters changed with aging. Hyperopic shift, shallowing anterior chamber depth, and reduction of corneal endothelial cell density were only definitely related to age.Keywords: corneal endothelial cell density, hyperopic, corneal curvatures, axial length, anterior chamber depth